Trade liberalization and technical efficiency in the Indonesian chemicals industry - Suatmi, B.; Bloch, Harry; Salim, Ruhul (Routledge, 2017)
This article examines the impact of trade reform on technical efficiency on the Indonesian chemicals industry using firm-level panel data. The effects of trade reform on technical efficiency are analysed using a stochastic frontier approach. Two variables represent trade reform in this model: effective rate of protection (ERP) and import ratio (IMP). The findings of the present study suggest that both trade reform variables have significant effects on technical efficiency. The coefficient of ERP has a positive sign and is statistically significant, which means that an increase in ERP increases the inefficiency (or decreases the technical efficiency) of firms in the chemicals industry. The coefficient of IMP is negative and statistically significant, which represents the negative impact of IMP on technical inefficiency (or positive on technical efficiency). Thus, trade reform, a reduction in ERP or an increase in IMP, has an unambiguously positive effect on technical efficiency in the Indonesian chemicals industry.